Potential sources of cessation support for high smoking prevalence groups: a qualitative study - Parnell, A.; Box, E.; Bonevski, B.; Slevin, Terry; Anwar-McHenry, J.; Chapman, L.; Pettigrew, Simone (Wiley-Blackwell Publishing Asia, 2019)
Objective: This study aimed to: i) explore potential sources of cessation support as nominated by disadvantaged smokers; and ii) identify factors influencing decisions to use these sources. Methods: Semi-structured interviews were conducted with 84 smokers accessing community service organisations from the alcohol and other drugs, homeless, and mental health sectors. Transcripts were coded and thematically analysed. Results: Doctors emerged as the most commonly recognised source of cessation support, followed by Quitline, community service organisation staff; and online resources. The main factors contributing to the possible use of these sources of support were identified as awareness, perceived usefulness and anticipated emotional support. Conclusions: The results suggest that doctors are an important group to consider when developing cessation interventions for disadvantaged smokers due to their recognised ability to provide practical and emotional support. However, efforts are needed to ensure doctors are aware of the benefits of cessation for these groups. Community service organisations appear to be another potentially effective source of cessation support for disadvantaged smokers. Implications for public health The results indicate that cessation interventions among high-priority groups should endeavour to provide personalised emotional and practical support. Doctors and community service organisation staff appear to be well-placed to deliver this support.